Spliced genes in muscle from Nelore Cattle and their association with carcass and meat quality - Silva, Danielly B. S. [UNESP]; Fonseca, Larissa F. S. [UNESP]; Pinheiro, Daniel G. [UNESP]; Magalhães, Ana F. B. [UNESP]; Muniz, Maria M. M. [UNESP]; Ferro, Jesus A. [UNESP]; Baldi, Fernando [UNESP]; Chardulo, Luis A. L. [UNESP]; Schnabel, Robert D.; Taylor, Jeremy F.; Albuquerque, Lucia G. [UNESP] (My University, 2020)
Transcript data obtained by RNA-Seq were used to identify differentially expressed alternatively spliced genes in ribeye muscle tissue between Nelore cattle that differed in their ribeye area (REA) or intramuscular fat content (IF). A total of 166 alternatively spliced transcripts from 125 genes were significantly differentially expressed in ribeye muscle between the highest and lowest REA groups (p ≤ 0.05). For animals selected on their IF content, 269 alternatively spliced transcripts from 219 genes were differentially expressed in ribeye muscle between the highest and lowest IF animals. Cassette exons and alternative 3′ splice sites were the most frequently found alternatively spliced transcripts for REA and IF content. For both traits, some differentially expressed alternatively spliced transcripts belonged to myosin and myotilin gene families. The hub transcripts were identified for REA (LRRFIP1, RCAN1 and RHOBTB1) and IF (TRIP12, HSPE1 and MAP2K6) have an important role to play in muscle cell degradation, development and motility. In general, transcripts were found for both traits with biological process GO terms that were involved in pathways related to protein ubiquitination, muscle differentiation, lipids and hormonal systems. Our results reinforce the biological importance of these known processes but also reveal new insights into the complexity of the whole cell muscle mRNA of Nelore cattle.